Analysis of ultrasonic seam tensile properties of thermal bonded nonwoven fabrics - (:unkn) unknown (Association Nonwoven Fabrics Industry, 2014)
Ultrasonic seam strength and elongation at break properties of thermal bonded nonwoven fabrics are discussed in this study; and the effects of fiber type, fabric area density, and roller type on ultrasonic tensile properties of nonwoven fabrics are reported. Polypropylene (PP), Polyester (PES), and Polyamide-Polyester (70% PA-30%PES) blend of thermal bonded nonwoven fabrics were used, and the seam strength and elongation at break were measured and the obtained data were evaluated. At the end of the experimental studies, the data from the ultrasonic tensile properties of thermal bonded nonwoven fabrics which were made of different fibers and same production method were evaluated in order to determine the tensile properties which lead to the best result. The experimental results show that the PP thermal bonded nonwoven fabric tended to provide the best seam strength and elongation at break values. © 2014, Association Nonwoven Fabrics Industry. All rights reserved.